The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3945/jn.115.211136
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Choline Status, but Not Fetal Genotype, Influences Cord Plasma Choline Metabolite Concentrations

Abstract: These data collectively indicate that maternal choline status, but not fetal genotype, influences cord plasma concentrations of choline metabolites. This trial was registered at clinicaltrials.gov as NCT02244684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
7
24
0
Order By: Relevance
“…, prior to the start of the intervention) was substantially <480 mg/d; otherwise, if usual choline intake was approximately equal to 480 mg/d, then all participants would have had the same duration of exposure to that amount of choline throughout pregnancy, regardless of the number of days the intervention was administered. This inference is consistent with the evidence, discussed above, indicating that the average choline intake of pregnant women in the U.S. is ~300‐350 mg choline/d, with fewer than 25% of women consuming the adequate intake (AI) level (3941). Considered in that light, the intake duration effect we report suggests that, even a modest increase in typical maternal choline intake during pregnancy would be beneficial for infant information processing speed, with possible long‐term benefits for offspring cognitive function throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…, prior to the start of the intervention) was substantially <480 mg/d; otherwise, if usual choline intake was approximately equal to 480 mg/d, then all participants would have had the same duration of exposure to that amount of choline throughout pregnancy, regardless of the number of days the intervention was administered. This inference is consistent with the evidence, discussed above, indicating that the average choline intake of pregnant women in the U.S. is ~300‐350 mg choline/d, with fewer than 25% of women consuming the adequate intake (AI) level (3941). Considered in that light, the intake duration effect we report suggests that, even a modest increase in typical maternal choline intake during pregnancy would be beneficial for infant information processing speed, with possible long‐term benefits for offspring cognitive function throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…OCTN2 is also responsible for carnitine intake in the placental tissue 22 . In general the clear increase in various trimethylated compounds may indicate the fetus’s high demand for choline and methyl donors, as has been suggested also earlier 30 . Previously, the rise in maternal plasma choline concentrations during pregnancy has been shown to reflect the mobilization of maternal hepatic choline stores and increase in estrogen.…”
Section: Discussionsupporting
confidence: 62%
“…Maternal plasma betaine have been found to remain constant from twenty-two gestational weeks to the rest of pregnancy (28,29) , a stage covering the period of our blood sample collection. A strong correlation between maternal betaine status and cord blood betaine status was observed (30) . Evidence from animal and human adult betaine supplementation trials as well as the GUSTO study suggested that the possible mechanisms of the observed decrease in birth weight related to betaine may involve adiposity reductions in infants (19,31,32) .…”
Section: Discussionmentioning
confidence: 91%
“…Associations between choline status with outcomes might be masked because we collected blood samples in a pregnancy stage during which plasma choline is increasing. Furthermore, it should also be noted that maternal plasma choline at delivery was not associated with cord plasma choline (30) .…”
Section: Discussionmentioning
confidence: 95%